FeNiHo / carbon nanofiber composite absorber and preparation method thereof, absorbing material and preparation method thereof

The preparation of FeNiHo/carbon nanofiber composite absorber through electrospinning technology and post-heat treatment process has solved the problems of poor impedance matching and poor absorption performance of traditional absorbing materials, and achieved strong absorption, wide frequency and low density absorption performance, and had the ability to adjust the absorption frequency in real time.

CN118812921BActive Publication Date: 2025-03-07INNER MONGOLIA UNIV OF SCI & TECH

Patent Information

Application Number
CN202411039577.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2025-03-07
Estimated Expiration
2044-07-31

AI Technical Summary

Technical Problem

In the prior art, traditional absorber materials and carbon-based absorber materials have poor impedance matching, poor absorption performance, and cannot adjust the absorption frequency in real time.

Method used

Electrospinning technology combined with post-stage heat treatment process is used to prepare FeNiHo/carbon nanofiber composite wave absorber, and nanofiber film is obtained by electrospinning, and pre-oxidation and carbonization are performed to form FeNiHo/carbon nanofiber composite wave absorber. The absorber consists of FeNiHo alloy nanoparticles and carbon nanofibers. The FeNiHo alloy nanoparticles are coated with an oxide layer to improve the absorbing performance.

Benefits of technology

It realizes strong absorption, wide frequency and low density absorption performance, improves the impedance matching performance and electromagnetic wave attenuation capability of carbon nanofibers, can adjust the absorption frequency in real time, and the preparation process is safe and simple, low cost, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118812921B_ABST
    Figure CN118812921B_ABST
Patent Text Reader

Abstract

The present invention provides a FeNiHo / carbon nanofiber composite absorber and a preparation method thereof, an absorbent material and a preparation method thereof, and belongs to the technical field of electromagnetic wave absorbing materials. The present invention first mixes iron salt, nickel salt, holmium salt and polyvinyl pyrrolidone in a mixed solvent, and electrostatically spins the obtained spinning precursor solution to obtain a nanofiber membrane; the nanofiber membrane is sequentially subjected to pre-oxidation treatment and carbonization treatment to obtain a FeNiHo / carbon nanofiber composite absorber. The FeNiHo / carbon nanofiber composite absorber, paraffin and petroleum ether are mixed, and then pressed and irradiated with ultraviolet light to obtain an absorbing material. The FeNiHo alloy nanoparticles in the composite absorber improve the impedance matching performance and electromagnetic wave attenuation ability of the carbon nanofiber. The obtained absorbing material can achieve the purpose of real-time adjustment of the absorption frequency by irradiation with ultraviolet light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electromagnetic wave absorbing materials, and in particular to a FeNiHo / carbon nanofiber composite absorbing agent and a preparation method thereof, and an absorbing material and a preparation method thereof. Background Art

[0002] With the rapid development of science and technology, electromagnetic waves have been used in information communication, medical treatment and military affairs, bringing great convenience to mankind. However, in addition to serving mankind, these information carriers also seriously affect electromagnetic safety. Although traditional metal-based absorbers show high magnetic loss and strong absorption capacity to a certain extent, their high density and low stability have seriously hindered their further development. Therefore, it is urgent to manufacture effective microwave absorbing materials to achieve the characteristics of "thin, light, wide and strong". Magnetic materials / carbon composites can not only achieve ideal impedance matching through the synergistic effect of magnetic loss and dielectric loss and multi-dimensional and multi-scale morphology, but also overcome the disadvantage of high density of magnetic materials. On the other hand, the method for adjusting the absorption frequency of traditional microwave absorbing materials mainly relies on increasing the thickness of the absorbing material, which cannot achieve real-time regulation. In view of the above requirements, it is of great significance to study a FeNiHo / carbon nanofiber composite absorber and its preparation method, absorbing material and its preparation method. Summary of the invention

[0003] The object of the present invention is to provide a FeNiHo / carbon nanofiber composite absorber and a preparation method thereof, an absorbing material and a preparation method thereof, so as to solve the problems in the prior art that traditional absorbing materials and carbon-based absorbing materials have poor impedance matching, poor absorption performance and cannot adjust the absorption frequency in real time.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a FeNiHo / carbon nanofiber composite absorber, comprising the following steps:

[0006] (1) mixing iron salt, nickel salt, holmium salt and polyvinyl pyrrolidone in a mixed solvent, and electrospinning the obtained spinning precursor solution to obtain a nanofiber membrane;

[0007] (2) The nanofiber membrane is subjected to pre-oxidation treatment and carbonization treatment in sequence to obtain a FeNiHo / carbon nanofiber composite absorber.

[0008] Preferably, in step (1), the iron salt comprises one or more of ferric nitrate, ferric chloride and ferric sulfate; the nickel salt comprises one or more of nickel acetate, nickel nitrate and nickel sulfate; the holmium salt comprises holmium nitrate and / or holmium acetate; and the molar ratio of the iron salt, the nickel salt and the holmium salt is 9-18:0.75-1.5:0.25-0.5.

[0009] Preferably, in step (1), the molar mass ratio of the iron salt to polyvinyl pyrrolidone is 9-18 mmol:4-8 g; the mass volume ratio of the polyvinyl pyrrolidone to the mixed solvent is 4-8 g:5-20 mL; and the mixed solvent is made of N,N-dimethylformamide and anhydrous ethanol.

[0010] Preferably, in step (1), the positive voltage of electrospinning is 15 to 20 kV, the negative voltage of electrospinning is -5 to -1 kV, the pushing speed of electrospinning is 0.05 to 0.4 mm / min, the receiving distance of electrospinning is 15 to 20 cm, and the receiving speed of electrospinning is 20 to 40 rpm.

[0011] Preferably, in step (2), the temperature of the pre-oxidation treatment is 250 to 350° C., and the time of the pre-oxidation treatment is 1 to 3 hours.

[0012] Preferably, in step (2), the temperature of the carbonization treatment is 600 to 1000° C., and the time of the carbonization treatment is 1 to 4 hours.

[0013] The present invention provides a FeNiHo / carbon nanofiber composite absorber prepared by the preparation method of the FeNiHo / carbon nanofiber composite absorber described above, wherein the FeNiHo / carbon nanofiber composite absorber consists of FeNiHo alloy nanoparticles and carbon nanofibers, wherein the FeNiHo alloy nanoparticles are coated with an oxide layer.

[0014] The invention provides a wave absorbing material, which comprises paraffin, petroleum ether and the above-mentioned FeNiHo / carbon nanofiber composite wave absorbing agent.

[0015] The present invention also provides a method for preparing the above-mentioned absorbing material, wherein paraffin, petroleum ether and FeNiHo / carbon nanofiber composite absorber are mixed, and then pressed and irradiated with ultraviolet light in sequence to obtain the absorbing material.

[0016] Preferably, the intensity of the ultraviolet light irradiation is 80-120 μW / cm 2 The UV light irradiation time is 1 to 200 seconds.

[0017] Beneficial effects of the present invention:

[0018] (1) The present invention adopts electrostatic spinning technology combined with a post-heat treatment process to prepare a FeNiHo / carbon nanofiber composite absorber. The FeNiHo alloy nanoparticles in the FeNiHo / carbon nanofiber composite absorber are coated with an oxide layer, which can improve the corrosion resistance and oxidation resistance of the internal FeNiHo alloy nanoparticles. The FeNiHo / carbon nanofiber composite absorber has the characteristics of strong absorption, wide frequency, and low density, and has good absorbing performance.

[0019] (2) In the FeNiHo / carbon nanofiber composite absorber of the present invention, the FeNiHo alloy nanoparticles improve the impedance matching performance and electromagnetic wave attenuation capability of the carbon nanofibers, and the electromagnetic parameters are effectively regulated by adding the FeNiHo alloy nanoparticles.

[0020] (3) The absorbing material prepared by the present invention can achieve the purpose of adjusting the absorption frequency in real time through the irradiation of ultraviolet light.

[0021] (4) The absorbing material of the present invention has the characteristics of light weight, thin thickness, wide absorption frequency band and strong absorption capacity. In addition, the preparation process provided by the present invention is safe and simple, with low production cost and short cycle, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The XRD diagram of the FeNiHo / carbon nanofiber composite absorber prepared in Examples 1 to 3;

[0023] Figure 2 This is a transmission electron microscope image of the FeNiHo / carbon nanofiber composite absorber prepared in Example 1;

[0024] Figure 3 This is a transmission electron microscope image of the FeNiHo / carbon nanofiber composite absorber prepared in Example 2;

[0025] Figure 4 This is a transmission electron microscope image of the FeNiHo / carbon nanofiber composite absorber prepared in Example 3;

[0026] Figure 5 The transmission electron microscope image of FeNiHo alloy nanoparticles in the FeNiHo / carbon nanofiber composite absorber prepared in Example 3;

[0027] Figure 6 3D reflection loss diagram of the ring obtained in Example 1;

[0028] Figure 7 3D reflection loss diagram of the ring obtained in Example 2;

[0029] Figure 8 3D reflection loss diagram of the ring obtained in Example 3;

[0030] Fig. 9 This is a comparison diagram of the two-dimensional reflection curves of the adjustment frequency and absorption frequency of the absorbing material prepared in Example 3 after being irradiated with ultraviolet light for different periods of time. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing a FeNiHo / carbon nanofiber composite absorber, comprising the following steps:

[0032] (1) mixing iron salt, nickel salt, holmium salt and polyvinyl pyrrolidone in a mixed solvent, and electrospinning the obtained spinning precursor solution to obtain a nanofiber membrane;

[0033] (2) The nanofiber membrane is subjected to pre-oxidation treatment and carbonization treatment in sequence to obtain a FeNiHo / carbon nanofiber composite absorber.

[0034] In the present invention, in the step (1), the iron salt comprises one or more of ferric nitrate, ferric chloride and ferric sulfate, preferably ferric nitrate and / or ferric chloride, and more preferably ferric nitrate; the nickel salt comprises one or more of nickel acetate, nickel nitrate and nickel sulfate, preferably nickel acetate and / or nickel nitrate, and more preferably nickel acetate; the holmium salt comprises holmium nitrate and / or holmium acetate, and preferably holmium nitrate; the molar ratio of the iron salt, the nickel salt and the holmium salt is 9-18:0.75-1.5:0.25-0.5, preferably 9:0.75:0.25, 13.5:1.125:0.375 or 18:1.5:0.5, and more preferably 18:1.5:0.5.

[0035] In the present invention, in the step (1), the molar mass ratio of the iron salt to the polyvinyl pyrrolidone is 9-18 mmol: 4-8 g, preferably 13.5-18 mmol: 5-7 g, and more preferably 18 mmol: 6 g; the mass volume ratio of the polyvinyl pyrrolidone to the mixed solvent is 4-8 g: 5-20 mL, preferably 5-7 g: 8-15 mL, and more preferably 6 g: 10-12 mL; the mixed solvent is made of N,N-dimethylformamide and anhydrous ethanol, and the volume ratio of the N,N-dimethylformamide to anhydrous ethanol is 1:1-3, preferably 1:1-2, and more preferably 1:1.

[0036] In the present invention, in the step (1), the positive voltage of electrospinning is 15 to 20 kV, preferably 16 to 18 kV, and more preferably 17 kV; the negative voltage of electrospinning is -5 to -1 kV, preferably -4 to -2 kV, and more preferably -3 to -2.5 kV; the push speed of electrospinning is 0.05 to 0.4 mm / min, preferably 0.1 to 0.3 mm / min, and more preferably 0.2 mm / min; the receiving distance of electrospinning is 15 to 20 cm, preferably 16 to 19 cm, and more preferably 17 to 18 cm; the receiving speed of electrospinning is 20 to 40 rpm, preferably 25 to 35 rpm, and more preferably 30 rpm.

[0037] In the present invention, in step (2), the temperature of the pre-oxidation treatment is 250-350°C, preferably 280-340°C, and more preferably 300-330°C. The time of the pre-oxidation treatment is 1-3h, preferably 1.5-2.5h, and more preferably 1.5-2h.

[0038] In the present invention, the carbonization treatment is carried out in a nitrogen-hydrogen mixed atmosphere, wherein the volume ratio of nitrogen to hydrogen is preferably 95:5.

[0039] In the present invention, in step (2), the temperature of the carbonization treatment is 600-1000°C, preferably 650-900°C, more preferably 700-800°C, and the time of the carbonization treatment is 1-4h, preferably 1.5-3.5h, more preferably 2-3h.

[0040] The present invention provides a FeNiHo / carbon nanofiber composite absorber prepared by the preparation method of the FeNiHo / carbon nanofiber composite absorber described above, wherein the FeNiHo / carbon nanofiber composite absorber consists of FeNiHo alloy nanoparticles and carbon nanofibers, wherein the FeNiHo alloy nanoparticles are coated with an oxide layer.

[0041] In the present invention, the FeNiHo / carbon nanofiber composite absorber presents a multi-dimensional and multi-scale interface morphology, the FeNiHo alloy nanoparticles are evenly distributed inside the carbon nanofibers, and the FeNiHo alloy nanoparticles have strong corrosion resistance and oxidation resistance.

[0042] In the present invention, the diameter distribution range of the FeNiHo / carbon nanofiber composite absorber is 0.5-2 μm.

[0043] The invention provides a wave absorbing material, which comprises paraffin, petroleum ether and the above-mentioned FeNiHo / carbon nanofiber composite wave absorbing agent.

[0044] The present invention also provides a method for preparing the above-mentioned absorbing material, wherein paraffin, petroleum ether and FeNiHo / carbon nanofiber composite absorber are mixed, and then pressed and irradiated with ultraviolet light in sequence to obtain the absorbing material.

[0045] In the present invention, firstly, the FeNiHo / carbon nanofiber composite absorber and paraffin are mixed, wherein the filling rate of the FeNiHo / carbon nanofiber composite absorber is 20-30%, preferably 25%.

[0046] In the present invention, the mass ratio of paraffin wax to petroleum ether is 0.05-0.15:0.1-0.3, preferably 0.07-0.12:0.2, and more preferably 0.09-0.11:0.2.

[0047] In the present invention, the intensity of the ultraviolet light irradiation is 80-120 μW / cm 2 , preferably 90 to 110 W / cm 2 , more preferably 100W / cm 2 The ultraviolet light irradiation time is 1 to 200 seconds, preferably 20 to 100 seconds, and more preferably 40 to 80 seconds.

[0048] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0049] Example 1

[0050] 9 mmol of ferric nitrate, 0.75 mmol of nickel acetate and 0.25 mmol of holmium nitrate were added to 20 mL of a mixed solvent (a mixed solvent of N,N-dimethylformamide and anhydrous ethanol, wherein the volume ratio of N,N-dimethylformamide and anhydrous ethanol was 1:1), and ultrasonicated for 30 min until completely dissolved to obtain a uniform solution, and then 6 g of polyvinyl pyrrolidone (K90) was added and stirred at room temperature for 12 h to obtain a uniform spinning precursor solution.

[0051] A 10mL syringe was used to absorb a uniform spinning precursor solution for electrospinning. The electrospinning parameters were set as follows: positive voltage of +17kV, negative voltage of -2.5kV, pushing speed of 0.2mm / min, receiving distance of 18cm, and receiving speed of 30rpm to obtain a nanofiber membrane; the nanofiber membrane was pre-oxidized at 330°C for 1.5h, and finally the pre-oxidation product was placed in a nitrogen-hydrogen mixed atmosphere (the volume ratio of nitrogen and hydrogen was 95:5), and carbonized at 700°C for 2h to obtain a FeNiHo / carbon nanofiber composite absorber.

[0052] 0.09 g of paraffin wax and 0.03 g of FeNiHo / carbon nanofiber composite absorber were mixed evenly, and the filling rate of FeNiHo / carbon nanofiber composite absorber in the obtained mixture was 25%. The above mixture was mixed with 0.2 g of petroleum ether, and after mixing evenly, it was put into a steel mold and pressed into a ring with an outer diameter of 7 mm and an inner diameter of 3 mm, waiting for testing.

[0053] Example 2

[0054] 13.5 mmol of ferric nitrate, 1.125 mmol of nickel acetate and 0.375 mmol of holmium nitrate were added to 20 mL of a mixed solvent (a mixed solvent of N,N-dimethylformamide and anhydrous ethanol, wherein the volume ratio of N,N-dimethylformamide to anhydrous ethanol was 1:1), and ultrasonicated for 30 min until completely dissolved to obtain a uniform solution, and then 6 g of polyvinyl pyrrolidone (K90) was added and stirred at room temperature for 12 h to obtain a uniform spinning precursor solution.

[0055] A 10mL syringe was used to absorb a uniform spinning precursor solution for electrospinning. The electrospinning parameters were set as follows: positive voltage of +17kV, negative voltage of -2.5kV, pushing speed of 0.2mm / min, receiving distance of 18cm, and receiving speed of 30rpm to obtain a nanofiber membrane; the nanofiber membrane was pre-oxidized at 330°C for 1.5h, and finally the pre-oxidation product was placed in a nitrogen-hydrogen mixed atmosphere (the volume ratio of nitrogen and hydrogen was 95:5), and carbonized at 700°C for 2h to obtain a FeNiHo / carbon nanofiber composite absorber.

[0056] 0.09 g of paraffin wax and 0.03 g of FeNiHo / carbon nanofiber composite absorber were mixed evenly, and the filling rate of FeNiHo / carbon nanofiber composite absorber in the obtained mixture was 25%. The above mixture was mixed with 0.2 g of petroleum ether, and after mixing evenly, it was put into a steel mold and pressed into a ring with an outer diameter of 7 mm and an inner diameter of 3 mm, waiting for testing.

[0057] Example 3

[0058] 18 mmol of ferric nitrate, 1.5 mmol of nickel acetate and 0.5 mmol of holmium nitrate were added to 20 mL of a mixed solvent (a mixed solvent of N,N-dimethylformamide and anhydrous ethanol, wherein the volume ratio of N,N-dimethylformamide to anhydrous ethanol was 1:1), and ultrasonicated for 30 min until completely dissolved to obtain a uniform solution, and then 6 g of polyvinyl pyrrolidone (K90) was added and stirred at room temperature for 12 h to obtain a uniform spinning precursor solution.

[0059] A 10mL syringe was used to absorb a uniform spinning precursor solution for electrospinning. The electrospinning parameters were set as follows: positive voltage of +17kV, negative voltage of -2.5kV, pushing speed of 0.2mm / min, receiving distance of 18cm, and receiving speed of 30rpm to obtain a nanofiber membrane; the nanofiber membrane was pre-oxidized at 330°C for 1.5h, and finally the pre-oxidation product was placed in a nitrogen-hydrogen mixed atmosphere (the volume ratio of nitrogen and hydrogen was 95:5), and carbonized at 700°C for 2h to obtain a FeNiHo / carbon nanofiber composite absorber.

[0060] 0.09 g of paraffin wax and 0.03 g of FeNiHo / carbon nanofiber composite absorber were mixed evenly, and the filling rate of FeNiHo / carbon nanofiber composite absorber in the obtained mixture was 25%. The above mixture was mixed with 0.2 g of petroleum ether, and after mixing evenly, it was put into a steel mold and pressed into a ring with an outer diameter of 7 mm and an inner diameter of 3 mm, waiting for testing.

[0061] Prepare multiple rings according to the above method, and then take 4 rings and irradiate them with ultraviolet light respectively. The intensity of ultraviolet light irradiation is 100W / cm 2 The irradiation times were 20s, 40s, 60s, and 80s respectively.

[0062] Example 4

[0063] 9 mmol of ferric nitrate, 0.75 mmol of nickel acetate and 0.25 mmol of holmium nitrate were added to 20 mL of a mixed solvent (a mixed solvent of N,N-dimethylformamide and anhydrous ethanol, wherein the volume ratio of N,N-dimethylformamide to anhydrous ethanol was 1:3), and ultrasonicated for 30 min until completely dissolved to obtain a uniform solution, and then 6 g of polyvinyl pyrrolidone (K90) was added and stirred at room temperature for 12 h to obtain a uniform spinning precursor solution.

[0064] A 10mL syringe was used to absorb a uniform spinning precursor solution for electrospinning. The electrospinning parameters were set as follows: positive voltage of +20kV, negative voltage of -1kV, pushing speed of 0.4mm / min, receiving distance of 15cm, and receiving speed of 20rpm to obtain a nanofiber membrane; the nanofiber membrane was pre-oxidized at 350°C for 1h, and finally the pre-oxidation product was placed in a nitrogen-hydrogen mixed atmosphere (the volume ratio of nitrogen and hydrogen was 95:5), and carbonized at 1000°C for 1h to obtain a FeNiHo / carbon nanofiber composite absorber.

[0065] 0.09g paraffin wax and 0.03g FeNiHo / carbon nanofiber composite absorber were mixed evenly, and the filling rate of FeNiHo / carbon nanofiber composite absorber in the obtained mixture was 25%. The above mixture was mixed with 0.2g petroleum ether, and after mixing evenly, it was put into a steel mold and pressed into a ring with an outer diameter of 7mm and an inner diameter of 3mm. The ring was irradiated with ultraviolet light, and the intensity of ultraviolet light irradiation was 100W / cm 2 , the irradiation time is 100s, and the light-absorbing material is obtained.

[0066] Example 5

[0067] 9 mmol of ferric nitrate, 0.75 mmol of nickel acetate and 0.25 mmol of holmium nitrate were added to 20 mL of a mixed solvent (a mixed solvent of N,N-dimethylformamide and anhydrous ethanol, wherein the volume ratio of N,N-dimethylformamide and anhydrous ethanol was 1:1), and ultrasonicated for 30 min until completely dissolved to obtain a uniform solution, and then 6 g of polyvinyl pyrrolidone (K90) was added and stirred at room temperature for 12 h to obtain a uniform spinning precursor solution.

[0068] A 10mL syringe was used to absorb a uniform spinning precursor solution for electrospinning. The electrospinning parameters were set as follows: positive voltage of +15kV, negative voltage of -5kV, pushing speed of 0.05mm / min, receiving distance of 20cm, and receiving speed of 40rpm to obtain a nanofiber membrane; the nanofiber membrane was pre-oxidized at 250°C for 3h, and finally the pre-oxidation product was placed in a nitrogen-hydrogen mixed atmosphere (the volume ratio of nitrogen and hydrogen was 95:5), and carbonized at 600°C for 4h to obtain a FeNiHo / carbon nanofiber composite absorber.

[0069] 0.09g paraffin wax and 0.03g FeNiHo / carbon nanofiber composite absorber were mixed evenly, and the filling rate of FeNiHo / carbon nanofiber composite absorber in the obtained mixture was 25%. The above mixture was mixed with 0.2g petroleum ether, and after mixing evenly, it was put into a steel mold and pressed into a ring with an outer diameter of 7mm and an inner diameter of 3mm. The ring was irradiated with ultraviolet light, and the intensity of ultraviolet light irradiation was 100W / cm 2 , the irradiation time is 150s, and the light-absorbing material is obtained.

[0070] Figure 1 The XRD diagram of the FeNiHo / carbon nanofiber composite absorber prepared in Examples 1 to 3 is shown in FIG. Figure 1 It can be seen that the FeNiHo / carbon nanofiber composite absorbers all show the coexistence of taenite, nickel stone and amorphous carbon phases, and their crystallinity is good.

[0071] Figures 2 to 4The transmission electron microscope images of the FeNiHo / carbon nanofiber composite absorbers prepared in Examples 1 to 3 show that the FeNiHo / carbon nanofiber composite absorbers all present typical fiber shapes. Figure 4 It can be seen that the FeNiHo / carbon nanofiber composite absorber of Example 3 has a different morphology from that of Examples 1 and 2, and becomes a fiber structure with multi-dimensional and multi-scale interfaces. This multi-scale interface improves the anti-matching characteristics of the absorbing material, forms more dipoles at the interface, and enhances the absorption capacity of electromagnetic waves.

[0072] The FeNiHo / carbon nanofiber composite absorber of Example 3 was stripped of carbon nanofibers and FeNiHo alloy nanoparticles by special means. High-resolution transmission electron microscopy (HRTEM) showed that the FeNiHo alloy nanoparticles had an obvious core-shell structure and a thin oxide layer on the outer layer, and the thickness of the oxide layer was distributed in the range of 2 to 10 nm.

[0073] The performance of the rings made in Examples 1 to 3 was measured, wherein the electromagnetic parameters were tested using the coaxial transmission reflection method, the testing instrument was Anritsu-MS46322B vector network analyzer, and the test frequency range was 2 to 18 GHz. The obtained electromagnetic parameters were input into the calculation software, and the wave absorption performance at a thickness of 2 to 3 mm was calculated by changing the calculation thickness.

[0074] The performance of the absorbing material of Example 3 after being irradiated with ultraviolet light for different times (0s, 20s, 40s, 60s, 80s) is shown in the following results: Fig. 9 As shown. Fig. 9 It can be seen that when the calculated thickness is 2.3 mm, the frequency of the strongest absorption peak of the absorbing material gradually moves to high frequency with the increase of ultraviolet light irradiation time, from 12.32 GHz at 0 s to 15.92 GHz at 80 s, moving to high frequency by 3.6 GHz. It can be seen that the present invention achieves the purpose of real-time regulation of the absorbing frequency by using ultraviolet light irradiation, breaking the traditional method of only changing the absorbing frequency by increasing the thickness of the absorbing material.

[0075] As can be seen from the above embodiments, the present invention provides a FeNiHo / carbon nanofiber composite absorber and a preparation method thereof, an absorbing material and a preparation method thereof. The present invention first mixes iron salt, nickel salt, holmium salt and polyvinyl pyrrolidone in a mixed solvent, and electrospins the obtained spinning precursor solution to obtain a nanofiber membrane; the nanofiber membrane is sequentially pre-oxidized and carbonized to obtain a FeNiHo / carbon nanofiber composite absorber. The above-mentioned FeNiHo / carbon nanofiber composite absorber, paraffin and petroleum ether are mixed and then pressed and irradiated with ultraviolet light to obtain an absorbing material. The FeNiHo alloy nanoparticles in the FeNiHo / carbon nanofiber composite absorber improve the impedance matching performance and electromagnetic wave attenuation ability of the carbon nanofiber, and the electromagnetic parameters are effectively regulated by adding the FeNiHo alloy nanoparticles. The obtained absorbing material achieves the purpose of real-time adjustment of the absorption frequency by irradiation with ultraviolet light.

[0076] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a FeNiHo / carbon nanofiber composite absorber, characterized in that: The steps include: (1) mixing iron salt, nickel salt, holmium salt and polyvinyl pyrrolidone in a mixed solvent, and electrospinning the obtained spinning precursor solution to obtain a nanofiber membrane; (2) pre-oxidation treatment and carbonization treatment are performed on the nanofiber membrane in sequence to obtain a FeNiHo / carbon nanofiber composite absorber; The molar ratio of the iron salt, the nickel salt and the holmium salt is 9 to 18: 0.75~1.5:0.25~0.5; The molar mass ratio of the iron salt to polyvinyl pyrrolidone is 9-18 mmol:4-8 g.

2. The method for preparing the FeNiHo / carbon nanofiber composite absorber according to claim 1, characterized in that: In the step (1), the iron salt comprises one or more of ferric nitrate, ferric chloride and ferric sulfate; the nickel salt comprises one or more of nickel acetate, nickel nitrate and nickel sulfate; and the holmium salt comprises holmium nitrate and / or holmium acetate.

3. The method for preparing the FeNiHo / carbon nanofiber composite absorber according to claim 2, characterized in that: In the step (1), the mass volume ratio of polyvinyl pyrrolidone to the mixed solvent is 4-8 g:5-20 mL; the mixed solvent is made of N,N-dimethylformamide and anhydrous ethanol.

4. The method for preparing the FeNiHo / carbon nanofiber composite absorber according to any one of claims 1 to 3, characterized in that: In the step (1), the positive voltage of electrospinning is 15 to 20 kV, the negative voltage of electrospinning is -5 to -1 kV, the pushing speed of electrospinning is 0.05 to 0.4 mm / min, the receiving distance of electrospinning is 15 to 20 cm, and the receiving speed of electrospinning is 20 to 40 rpm.

5. The method for preparing the FeNiHo / carbon nanofiber composite absorber according to claim 4, characterized in that: In the step (2), the temperature of the pre-oxidation treatment is 250 to 350° C., and the time of the pre-oxidation treatment is 1 to 3 hours.

6. The method for preparing the FeNiHo / carbon nanofiber composite absorber according to claim 2, 3 or 5, characterized in that: In the step (2), the temperature of the carbonization treatment is 600 to 1000° C., and the time of the carbonization treatment is 1 to 4 hours.

7. The FeNiHo / carbon nanofiber composite absorber prepared by the preparation method of the FeNiHo / carbon nanofiber composite absorber according to any one of claims 1 to 6, characterized in that: The FeNiHo / carbon nanofiber composite absorber consists of FeNiHo alloy nanoparticles and carbon nanofibers, wherein the FeNiHo alloy nanoparticles are coated with an oxide layer.

8. A wave absorbing material, characterized in that: The absorbing material comprises paraffin, petroleum ether and the FeNiHo / carbon nanofiber composite absorber according to claim 7.

9. The method for preparing the wave absorbing material according to claim 8, characterized in that: Paraffin, petroleum ether and FeNiHo / carbon nanofiber composite absorber are mixed, pressed and irradiated with ultraviolet light in sequence to obtain an absorbing material.

10. The method for preparing the absorbing material according to claim 9, characterized in that: The intensity of the ultraviolet light irradiation is 80-120 μW / cm 2 The UV light irradiation time is 1 to 200 seconds.

Citation Information

Patent Citations

  • Fe-Ni-based alloy absorbing material

    CN106607590A

  • FeNi / C nanofiber electromagnetic absorber and preparation method thereof

    CN108521755A

  • Cobalt-nickel-graphene composite wave-absorbing material and preparation method thereof

    CN111615320A

  • HCNFs-CoNi one-dimensional composite fiber and preparation method and application thereof

    CN117779238A

Cited By

  • Composite fiber absorbent and preparation method thereof

    CN121915529A